The first report of the occurrence of anthracnose disease caused by Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. on dragon fruit (Hylocereus spp.) in Peninsular Malaysia - Masyahit, Masanto; Sijam, Kamaruzaman; Awang, Yahya; Mohd Satar, Mohd Ghazali (Science Publications, 2009)
Problem statement: The increasing of dragon fruit (Hylocereus spp.) plantations in Malaysia enhances the researches on this crop, particularly focusing on its physico-chemical characteristics, great potential health benefits and nutritional value. However, its scientific report of disease is still lacking, primarily on anthracnose disease. This study was then conducted to investigate the distribution of anthracnose disease on dragon fruit and to correlate its occurrence with weather and cultural data. Approach: Survey and sampling were conducted on dragon fruit-growing areas in Peninsular Malaysia since December 2007 until August 2008 to measure the Disease Incidence (DI) and Disease Severity (DS). The diseased stem and fruit were sampled and brought to laboratory for isolation and identification. DI data were plotted with DS and then correlated using Pearson correlation with weather and cultural data. Results: Of the 43 surveyed-farms in 11 states, DI and DS were successfully recorded on three dragon fruit species from 36 farms (83.72%). The infected stem and fruit had reddish-brown lesions with chlorotic haloes symptoms. The lesion had brown centers and coalesced to rot. Based on its whitish-orange colony, septated hypae and capsule-like conidia and the pathogenicity test, the pathogen was identified as Colletotrichum gloeosporioides. One way ANOVA with DMRT test highlighted that the most disease occurrence was found in Malacca (mean of DI and DS, 57.30 and 21.20%), whereas the lowest in Kelantan state (mean of DI and DS, 6.70 and 4.30%). Pearson coefficient correlations were around 0.107-0.261 for relationships between disease occurrence and age of crops and acreage of farm, from-0.049 to-0.237 for disease prevalence with relative humidity and rainfall and around-0.012-0.173 for disease occurrence with monthly temperature, wind velocity and altitude. Conclusion: The occurrence of anthracnose on dragon fruit in Peninsular Malaysia was more influenced by environmental conditions and agricultural practices rather than climatic factors.